Audiologic follow up results of child with NGLY1 deficiency (Annals of Medical Research, 2023)
NGLY1 deficiency is a rare in which affected individuals show developmental delay/intellectual disability in the mild to profound range, epilepsy, auditory neuropathy, abnormal liver function, complex hyperkinetic movement disorder and poor growth. Here, we present the follow-up results of hearing status in a patient with NGLY1 deficiency.
Keywords: Auditory neuropathy; Cochlear microphonics; Congenital disorder of deglycosylation; NGLY1; Progressive hearing loss